Soluble Epoxide Hydrolase Inhibition and Epoxyeicosatrienoic Acid Treatment Improve Vascularization of Engineered Skin Substitutes. Issue 12 (December 2016) - Supp, Dorothy M.; Hahn, Jennifer M.; McFarland, Kevin L.; Combs, Kelly A.; Lee, Kin Sing Stephen; Inceoglu, Bora; Wan, Debin; Boyce, Steven T.; Hammock, Bruce D.
Abstract : Background: Autologous engineered skin substitutes comprised of keratinocytes, fibroblasts, and biopolymers can serve as an adjunctive treatment for excised burns. However, engineered skin lacks a vascular plexus at the time of grafting, leading to slower vascularization and reduced rates of engraftment compared with autograft. Hypothetically, vascularization of engineered skin grafts can be improved by treatment with proangiogenic agents at the time of grafting. Epoxyeicosatrienoic acids (EETs) are cytochrome P450 metabolites of arachidonic acid that are inactivated by soluble epoxide hydrolase (sEH). EETs have multiple biological activities and have been shown to promote angiogenesis. Inhibitors of sEH (sEHIs) represent attractive therapeutic agents because they increase endogenous EET levels. We investigated sEHI administration, alone or combined with EET treatment, for improved vascularization of engineered skin after grafting to mice. Methods: Engineered skin substitutes, prepared using primary human fibroblasts and keratinocytes, were grafted to full-thickness surgical wounds in immunodeficient mice. Mice were treated with the sEHI 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea (TPPU), which was administered in drinking water throughout the study period, with or without topical EET treatment, and were compared with vehicle-treated controls. Vascularization was quantified by image analysis of CD31-positive areas in tissue sections. Results: At 2 weeks after grafting, significantly increased vascularization was observed in the TPPU and TPPU + EET groups compared with controls, with no evidence of toxicity. Conclusions: The results suggest that sEH inhibition can increase vascularization of engineered skin grafts after transplantation, which may contribute to enhanced engraftment and improved treatment of full-thickness wounds. Abstract : Supplemental Digital Content is available in the text.